Remote Sensing and Modeling LENA2006. - Wißkirchen, Klaus; Kirschke, Stefanie; Günther, Kurt P. (2008)
Quantifying sources and sinks of climatological relevant trace gases as well as understanding their exchange between atmosphere and land surfaces has become essential research topics in atmospheric sciences during the last years. High latitude ecosystems are most critically influenced by a changing climate. Modeling the terrestrial carbon cycle - net CO2 uptake by vegetation (Net Primary Productivity, NPP) as well as methane emissions from natural wetlands – is a powerful tool to study the impact of climate change. Uncertainties in the carbon budget of arctic ecosystems remain partly due to difficulties in assessing the spatially and temporally highly variable methane emissions of permafrost soils.